Dominant responses of bridge abutments. Issue 148 (September 2021) - Noè Gorini, Davide; Callisto, Luigi; Whittle, Andrew J.
Abstract: Under seismic conditions a bridge abutment can transfer significant inertial effects to the superstructure due to its interaction with a large volume of soil. These effects can lead to a marked dynamic amplification of the abutment response that should be accounted for in bridge design. In order to quantify these effects, we present analytical solutions for the modal characteristics of the soil-abutment system at small strains, expressed in terms of the vibration periods and mass participation factors for the approach embankment considering different directions of motion. The effect of nonlinear soil behaviour is also investigated through nonlinear numerical analyses of the soil-abutment system in OpenSees, which establish the dependence of the vibration periods on the intensity of the external perturbation. The numerical results were used as a benchmark to validate the analytical predictions at small strains; they can also provide some indication on the applicability of the analytical formulation at medium and large strain levels. The proposed method of dynamic identification can be used as a tool to evaluate the dynamic characteristics of bridge abutments, which can be in turn regarded as the inertial features of macroelement representations for abutments in the structural analysis of bridges. Highlights: Analytical approach for the dynamic identification of the soil-abutment system. Nonlinear soil behaviour investigated through numerical soil-abutment interaction models. Inertial effects in the embankment control the dynamic response of the abutment. Inertial effects controlled by the fundamental modes of the embankment. Lengthening of the dynamic response of the soil-abutment system function of the load direction.